Analysis of Budget Realization Reports in Assessing the Effectiveness and Efficiency of the Financial Performance of the Padangsidimpuan City Government - Badriah Daulay; Galih Supraja; Junawan (CV. Doki Course and Training, 2026)
This study aims to analyze the effectiveness and efficiency of the financial performance of the Padangsidimpuan City Government based on the Budget Realization Report (LRA) for the 2021–2024 period. The problem discussed in this study is the realization of fluctuating regional revenues and expenditures, which affects the stability of fiscal performance in achieving development goals. This study uses a descriptive quantitative method using an analysis of the ratio of effectiveness and efficiency in accordance with the Regulation of the Minister of Home Affairs No. 79 of 2018. The results show that financial performance in terms of effectiveness is categorized as effective, with an average ratio of above 90%, although it has decreased to a fairly effective level in 2023. Meanwhile, efficiency performance remained inefficient to inefficient, with ratios approaching or exceeding 100% in 2022 and 2023, implying that realized expenses were greater than revenue. These findings show that although the government has achieved satisfactory revenue realization, expenditure control has not been optimal. The study concludes that increasing regional revenue sources and implementing performance-based budgeting are important strategies to improve the effectiveness and efficiency of regional financial management.